Analysis of Cost Control on Food and Beverage in Mercure Resort Sanur - A.A Istri Yunita D.D.A.S; I M M Arsana; L M Wahyuni (Jurusan Akuntansi Politeknik Negeri Bali, 2019)
There is a deviation in the cost of food and beverages between the standard cost and the actual cost. Likewise, the weakness in controlling the cost of food and beverages. The purpose of this research, which is to identify the cause of conflict between the standard (standard cost ) with the actual cost (actual cost) food for breakfast and beverage for cocktail, and to know how the control costs of food for breakfast and beverage for cocktail. Data collection method used in this research, namely the observation, interview, and documentation. To achieve the quantitative analysis is used to calculate the cost of food and beverage are sold, cost variance, economic order quantity (EOQ), safety stock, maximum inventory and re-order point and descriptive-qualitative analysis technique. The results of research conducted by using data collected showed that 1) The deviation between standard cost and actual cost food for breakfast and beverage for cocktail is caused by increasing percentage of purchasing, any shortage of food for breakfast and beverage for cocktail and the amount of processing raw materials which is not accordance with the standard recipe. 2) Cost control of food and beverage is not optimally, where the employees are inconsistent in running the Standard Operating Procedure (SOP) and there are advantages and disadvantages of inventory due to those not do the calculation economically so that the differences are unfavorable.